The role of genetic counselling in genomic era - Tadikonda Sri Sravani; Q Hasan (Apollo Medicine)
Advances in genetic and genomic knowledge have revolutionized the diagnosis, management, treatment, and prevention of genetic disorders. Genetic counselors interpret and explain genomic information to patients, order the right genetic/genomic tests, calculate genetic risks, explain inheritance patterns, interpret genomic variants, and subsequently handle psychosocial and ethical issues raised within the individuals/families. Genetic counseling is a major part of the modern integrated modern genomic medicine academic and health-care unit. This review provides factual information on the principles and practices of genetic counseling.